Penerapan Pencarian Rute Tercepat Aliran Air Menggunakan Algoritma Bee Colony Optimization - Muhammad Alfi Yudhitiya (STMIK Budi Darma, 2018)
Water is one source for the needs of all living things. Water can also be used in a variety of ways, as in human life water can be used for consumption as a bath or for drinking. The Bee Colony Optimization algorithm is used in this study to solve problems regarding the search for clean water flow routes. This algorithm works to find each route that has been selected based on the path or route that has been determined in a system. The results obtained in this research are the Bee Colony Optimization Algorithm can be used to find the route of clean water flow. The number of bees that are determined greatly influences in finding and determining routes that can be accessed or accessed. The number of bees that are determined the greater the chance of finding a clean water flow search route